Iron-nickel bimetallic nanoparticles for reductive degradation of azo dye orange G in aqueous solution - Bokare, Alok D.; Chikate, Rajeev C.; Rode, Chandrashekhar V.; Paknikar, Kishore M. (Applied Catalysis B-Environmental, 2008)
The degradation of Orange G, a monoazo dye, in aqueous solutions was investigated using Fe-Ni bimetallic nanoparticles. Transmission electron microscopy (TEM) of as-synthesized nanoparticles showed the presence of spherical particles having a size of 20-40 nm. X-ray photoelectron spectroscopy (XPS) did not detect the presence of nickel on the nanoparticle surface, which suggested a uniform distribution of both metals inside the particle core. Batch experiments with a minimum nanocatalyst loading of 3 g/L showed complete dye degradation after 10 min of reaction time. The degradation efficiency was linearly dependent on the initial dye concentration, pH of the solution and total Fe-Ni catalyst concentration. The efficiency increased with increasing Fe-Ni concentration and decreasing pH of the solution, but decreased with an increase in the dye concentration. The degradation rate followed first order reaction kinetics with respect to the dye concentration. High performance liquid chromatography-mass spectrometry (HPLC-MS) analysis of the degradation products revealed that the degradation mechanism proceeds through a reductive cleavage of the azo linkage resulting in the formation of aniline and surface-adsorbed naphthol amine derivatives. The latter are subsequently hydroxylated through an oxidative process. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Azo Dye; Degradation; iron; Nanoparticles; Nickel

Influence of carbon based supports on selectivity behavior of diols and propanol in Ru catalyzed glycerol hydrogenolysis - Mane, Rasika B.; Patil, S.; Shirai, Masayuki; Rayalu, Sadhana S.; Rode, Chandrashekhar V. (Applied Catalysis B: Environmental, 2017)
Activated carbon (AC) and three graphite materials were studied as supports for Ru catalyzed glycerol hydrogenolysis to propanediols and 1-propanol. Structural characteristics of AC and graphite materials were found to greatly affect the reducibility and particle size of supported Ru and hence, the activity and product distribution in glycerol hydrogenolysis. XRD of graphite materials showed distinctly (002) plane having highly organized layered structure and the peak intensity decreased in the order of Ru/KS150 > Ru/HSAG100 > Ru/KS6 due to decrease in the graphite sheet thickness. In Raman, the intense D band in HSAG100 compared to that in KS6 and KS150 samples indicated its highly amorphous nature or mixed carbon hybridization. Glycerol conversion for Ru on AC was higher than that on graphite and among different graphites, it showed a descending activity order of Ru/KS6 > Ru/HSAG100 > Ru/KS150. The product distribution for AC and HSAG100 supported Ru was similar, giving 1-propanol (45%) alongwith 1,2-propanediol (1,2-PDO) (37%) and 1,3-propanediol (1,3-PDO) (9–11%). For graphite supports, availability of Ru although bigger in size (4–5 nm), would be higher on the surface than in case of AC which formed deep hydrogenolysis products like 1-, 2- propanol, ethanol etc.
Keywords: activated carbon; Amorphous carbon; catalysis; Glycerol; Glycerol conversions; Glycerol hydrogenolysis; graphite composites; Graphite supports; Hydrogenolysis; Hydrolysis; layered structures; Particle size; Product distributions; Propanediols; Propanol; Selectivity behavior; Structural characteristics; Structural effect; Structural effects

Integrated production of diesel fuel precursors from carbohydrates and 2-methylfuran over Sn-mont catalyst - Shinde, Suhas H.; Rode, Chandrashekhar V. (ChemistrySelect, 2018)
A TfOH-catalyzed highly efficient synthesis of biologically active (E)-2-cyanoacrylamides and 3-substituted azetidine-2,4-diones has been reported with 64-94% yields under metal-free conditions. The reaction proceeds through sequential Knoevenagel condensation/stereoselective in situ monohydration of nitrile or C-N cyclization protocol in one-pot. The attractive features of this tandem process are moderate reaction conditions, high atom economy, broad substrate scope, gram-scale reaction and ease of operation.